IN THE IMPLEMENTATION OF THE CUSTOMS SUPERVISION, THE PLACE OF THE CUSTOMS AUDIT. (International Bulletin of Applied Science and Technology, 2023)
This article explores the methods, objectives, types, and tasks of customs audits conducted by customs authorities, drawing on the experience of foreign countries.